Transformative Pastoral Leadership and Innovative Decisions in Church Restoration Based on the Tabernacle of David Restoration Amos 9: 11-12 - Rudy Budiatmaja; Alvonce Poluan (PT FORMOSA CENDEKIA GLOBAL, 2024)
Churches that provide pastoral leadership must always be transformative and their decisions must be innovative to become the center of God's presence and government on earth so that God reverses the current conditions of worship of Israel and the Tabernacle of David for church pastors who are transformative and make innovative decisions when talking about the worship of church pastors in Israel to God forever to be obedient and faithful. The descriptive qualitative method used in this research is in the form of various literature accompanied by various journal articles related to this research topic. The research results show that the Tabernacle of David is a symbol (typos) of the Church and the Restoration of the Tabernacle of David is seen as a continuation of God's promise to Abraham, which was then passed on to David as the Successor to Transformative Pastoral Leadership in an innovative decision with a broader scope which